Abscisic Acid Stimulation of Phospholipase D in the Barley Aleurone Is G-Protein-Mediated and Localized to the Plasma Membrane - Ritchie, Sian (American Society of Plant Physiologists, 2000)
We have previously determined that phospholipase D (PLD) is activated by abscisic acid (ABA), and this activation is required for the ABA response of the cereal aleurone cell. In this study, ABA-stimulated PLD activity was reconstituted in vitro in microsomal membranes prepared from aleurone protoplasts. The transient nature (20 min) and degree (1.5- to 2-fold) of activation in vitro were similar to that measured in vivo. Stimulation by ABA was only apparent in the membrane fraction and was associated with a fraction enriched in plasma membrane. These results suggest that an ABA receptor system and elements linking it to PLD activation are associated with the aleurone plasma membrane. The activation of PLD in vitro by ABA was dependent on the presence of GTP. Addition of GTPγS transiently stimulated PLD in an ABA-independent manner, whereas treatment with GDPβS or pertussis toxin blocked the PLD activation by ABA. Application of pertussis toxin to intact aleurone protoplasts inhibited the ability of ABA to activate PLD as well as antagonizing the ability of ABA to down-regulate gibberellic acid-stimulated α-amylase production. All of these data support the hypothesis that ABA stimulation of PLD activity occurs at the plasma membrane and is mediated by G-protein activity.